Influence of Domestic Natural Gas Production on the Development of National Economy - Писар, Н. Б. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The analysis of the state of the gas industry of Ukraine was conducted. The problems of energy independence of Ukraine were examined. The trend of natural gas production of Ukraine was presented. Gas reserves in existing domestic fields were estimated. The conceptual solutions for the development of the gas industry were proposed. The need for the increased governmental investment in the support and development of the natural gas producers was proved. The importance of development of domestic gas producing industry was highlighted in order to increase the overall level of economic security of Ukraine. The influence of the specific indicator of gas production on the ultimate level of development of the national economy was examined. The ways to overcome energy dependance of Ukraine were offered.